2021
DOI: 10.5433/1679-0375.2021v42n1p3
|View full text |Cite
|
Sign up to set email alerts
|

Time series forecasting using ARIMA for modeling of glioma growth in response to radiotherapy

Abstract: In present days, the growing number of people suffering from cancer has been a major cause for concern worldwide. Glioblastoma in particular, are primary tumors in glial cells located in the central nervous system. Because of this sensitive location, mathematical models have been studied and developed as alternative tools for analyzing tumor growth rates, assisting on the decision-making process for treatment dosage, without exposing the patient’s life. This paper presents two time series models to estimate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…An ARIMA model was used to capture the trend of pulse production in India by [ 19 ] to predict pulse production from 2020 to 2029 to bridge the gap between the supply and demand. Two time series models were employed to estimate the growth rate of glioblastoma in response to ionizing radiotherapy treatment in a comparative study presented by [ 20 ]. Their study showed that ARIMA performed better based on the mean square error (MSE) and MAPE values obtained than the Holt method.…”
Section: Introductionmentioning
confidence: 99%
“…An ARIMA model was used to capture the trend of pulse production in India by [ 19 ] to predict pulse production from 2020 to 2029 to bridge the gap between the supply and demand. Two time series models were employed to estimate the growth rate of glioblastoma in response to ionizing radiotherapy treatment in a comparative study presented by [ 20 ]. Their study showed that ARIMA performed better based on the mean square error (MSE) and MAPE values obtained than the Holt method.…”
Section: Introductionmentioning
confidence: 99%
“…Two mathematical models that describe the growth of gliomas were proposed in Leder et al (2014), Rockne et al (2009) and Swanson et al (2003). Both models were analyzed in Barbosa et al (2019), Silva et al (2016) and Souza et al (2015), and new approaches based on time series were suggested in Jesus et al (2014) and Silva et al (2021).…”
Section: Introductionmentioning
confidence: 99%